2012
DOI: 10.14295/bds.2012.v15i1.761
|View full text |Cite
|
Sign up to set email alerts
|

Mesiodistal and buccolingual crown size and height of deciduous teeth from a tooth bank in Brazil

Abstract: Objective: The size of primary teeth in the current Brazilian population has not been studied yet; the aim of this in vitro study was to document the size and variation of deciduous teeth from a tooth bank in São Paulo, Brazil. Methods: A sample of 1,095 deciduous teeth was obtained from a tooth bank at the Dental School of the University of Sao Paulo. The measurements were made with a digital caliper. Only unworn, undamaged teeth were measured. Results: At mesiodistal diameter, maxillary central incisor showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The sectional matrix bands of pediatric patients were 5.5 mm in height with a thickness of 0.0015 inches. According to Anfe TEA et al, 12 the height of the second deciduous molar is 5.501 mm, whereas the height of the sectional matrix bands for adults are 6.4 mm. This means that the pedodontic sectional matrix system height was formulated according to the height of the primary teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The sectional matrix bands of pediatric patients were 5.5 mm in height with a thickness of 0.0015 inches. According to Anfe TEA et al, 12 the height of the second deciduous molar is 5.501 mm, whereas the height of the sectional matrix bands for adults are 6.4 mm. This means that the pedodontic sectional matrix system height was formulated according to the height of the primary teeth.…”
Section: Discussionmentioning
confidence: 99%
“…As the Carthage crowns were 0.6mm shorter, they increased their age estimates by around four weeks. Human populations differ markedly in their tooth dimensions (Coughlin 1967;Yuen et al 1997;Hanihara & Ishida 2005;Anfe et al 2012), however, so any effect that heat might have on tooth size can be determined only by measuring the same teeth, pre-and post-cremation, as Deutsch and colleagues (Deutsch & Shapira 1987;Mayer et al 1990;Sydney-Zax et al 1991) and Soliel et al (1958) did. These studies revealed that shrinkage is at best negligible-a fact that Soliel et al used to identify pre-and perinates in their Carthage Tophet sample.…”
Section: Tooth-crown Shrinkagementioning
confidence: 99%